Law Protection on Wife Whose The Claims Fall Due To Husband Refuse His Recompensation On Implementing Of Divorce Pledge - Farhan Munirus Su'aidi; Abdullah Arief Cholil (Jurnal Daulat Hukum, 2019)
Decision granting a divorce pledge would fall if the husband was reluctant oath within six (6) months from the date of the hearing determination pledge. The fall verdict carries legal consequences fall anyway recompensation lawsuit filed by the wife. This study aimed to analyze the norms of protection of women and seek forms of law protection that can be given by the Court on the lawsuit wife his recompensation fall due reluctant husband dropped the divorce pledge.This type of research is normative by using the approach of law (statute approach) and conceptual (conceptual approach), using primary legal materials in the form of norms related to the protection of women and secondary legal materials such as the results of previous studies as well as data obtained through interviews is analyzed with the theory of protection and legal certainty as well as apply the legal principle Similia Similibus and Res Judicata Pro Veritate Habeturand the principle is simple, fast and low cost in the hope of giving recommendations that can be implemented to address the issues of law covered in the study.The results showed no norms whose provide law protection to wives whose husbands due to the fall lawsuit his recompensation pledge reluctantly dropped the divorce. The court can give law protection in the form of provision of facilities in the areas of administration and law of procedure for the wife who would resubmit its case in accordance with the legal principle is simple, fast and low cost.Keywords: Law Protection; Wife; Recompensation Lawsuit, Fall; Divorce Pledge.